CAN THE MUSLIM WORLD BORROW FROM INDONESIAN CONSTITUTIONAL REFORM? A Comparative Constitutional Approach (State Islamic University (UIN) of Sunan Ampel Surabaya, 2007)
This paper attempts to analytically examine the possibility of constitutional borrowing for the Muslim world regardless the differences in history, system, culture, language, and characteristics. It discusses this issue by looking at the arguments put forth by the opponents of comparative constitutional interpretation and their counter arguments. It will consider materials from Canada, USA, South Africa, Singapore, Malaysia, and Hungary, taking the position that constitutional borrowing can be justified. The paper argues that the 1999-2002 Indonesian constitutional reform should be taken into account by other Muslim countries in undertaking their constitutional reform. The substantive approach of the Shari‘ah that has been used in Indonesia has shown that Muslim world can reform its constitutions without the “assistance” of Western foreign policy. Indonesian constitutional reform has demonstrated that Islamic constitutionalism comes from within Islamic teaching and the Islamic community itself; it is a home grown product.